Tính chất quang của vật liệu nano ZnS: Cu, ZnS: Mn tổng hợp bằng phương pháp đồng kết tủa. - Lộc, Đinh Xuân; Vũ, Nguyễn; Hùng, Đỗ Mạnh (Vietnam Journal of Chemistry, 2012)
Mn and Cu doped ZnS nanocrystals were prepared by co-precipitation method in PVA and PMMA. Morphology and structure of materials were studied by FESEM and XRD. Luminescent spectra under different excitation wavelengths of 325 nm, 370 nm were investigated. Influence of activator concentration in ZnS:Cu were studied. Application potential in labeling will be discussed.